The influence of culture on destination image formation: a critical review - Hussin, Siti Rahayu; Mohd Fawzi, Nadiatul Natasha; Hashim, Haslinda (M/s Jupiter Global Business Research FZE, 2018)
Numerous theoretical frameworks have been developed to clarify the gap between the factors influencing image formation and destination image. Researchers have included few more factors being investigated in the relationships with destination image, and one factor that has gained increasing interest among researchers is cultural factor. Thus, the purpose of this paper is to enrich the body of knowledge on destination image by determining the cultural dimension having potential influence on destination image formation. In understanding tourist destination image, several streams of research has been conducted throughout the world. The first stream concerns what constitute a destination image, which is closely related to studies about the formation process of a tourist destination image. The second stream of research focuses on the factors influencing destination image. Under the second stream of research, many studies came up with mixed conclusion. i.e. there are factors that were found to have positive as well as negative influences on a tourist destination image. At the same time, the range of possible factors influencing the destination image include personal factors and stimulus factors. This current study explains a few of the most influential and commonly used analytical framework in destination image studies. It then analyses the factors that have been found to have some influence, positive or negative on the destination image formation such as personal factors (motivation and demographic characteristics) and stimulus factors (previous experience and information sources). This paper discussed studies which examine the relationship between culture and destination image with the intention to highlight the need to include the many facets of cultural factors in destination image formation as well as in understanding tourists’ behaviour.